Cultura en el PEFPI intereses del profesorado de español en formación inicial - Nicolás Martínez, Pilar (2021)
This study is framed in the context of the pre-service masters degrees in the teaching of languages (Spanish as a foreign language + Portuguese as a mother tongue, and Spanish + English as foreign languages) given at the Faculty of Arts and Humanities of the University of Porto. This training is preparation for the teaching of languages in lower and upper secondary education in Portugal.During the second year of these masters degrees, trainees conduct a teaching practicum in secondary schools and prepare a reflective portfolio related to this experience. One of the sections of this document is based on the descriptors of the European Portfolio for Student Teachers of Languages (EPOSTL).In this study, seventy-five trainee portfolios were collected from 2014 to 2019 and the written reflections related to the EPOSTL descriptors associated with "Culture" were selected for analysis. The objective was to analyse trainees' concerns, interests and perceptions about culture and its didactics in Spanish classroom, and in light of this, consider how to improve the training offered.